Visualising mouse neuroanatomy and function by metal distribution using laser ablation-inductively coupled plasma-mass spectrometry imaging1. Issue 10 (14th October 2015) - Paul, Bence; Hare, Dominic J.; Bishop, David P.; Paton, Chad; Nguyen, Van Tran; Cole, Nerida; Niedwiecki, Megan M.; Andreozzi, Erica; Vais, Angela; Billings, Jessica L.; Bray, Lisa; Bush, Ashley I.; et al.
<x xml:space="preserve">Abstract</x> Studying the neuroanatomy of the mouse brain using imaging mass spectrometry and chemometric analysis.